Transformational Educational Leadership Effect On Staff Members Engagement: The Mediating Impact Of Intrinsic Motivation - Kant, Dr. Shashi; Asefa, Kebede (Journal Research of Social Science, Economics, and Management, 2023)
Staff member’s engagement has been at the core of consideration for top management and scholars who stated that staff member’s engagement can be a key driver of an organization's business success. Many scholars have found in recent researches that a transformational educational leadership approach has a beneficial connection with staff member’s engagement. Therefore, this research oriented to investigate the connection of transformational educational leadership on staff members engagement through the mediating role of figurehead intrinsic enthusiasm. Researchers examine the information from a sample of 338 elevated education staff members working in the elevated educational institutes in Ethiopia by means of structural equation modeling (SEM) and confirmatory factor investigation (CFA) to examine the framed hypothesis. Afterward, the bootstrapping investigation was employed to verify the mediation examine in present research. The investigation manifested that transformational educational leadership approach had considered proficient impact on staff member’s engagement for the mediating role of intrinsic enthusiasm. The impact of transformational educational leadership on staff member’s engagement was found to be totally mediated by figurehead intrinsic enthusiasm. Hypothetically, present experiential investigation contributed to the novel knowledge on the exclusive mediating impacts of figurehead intrinsic motivation on the connections among transformational educational leadership and staff member’s engagement in the Ethiopia. Practically, present research has administrative connotation in the field of governmental administration, leadership and HRM.